The things they carried : a work of fiction - O'Brien, Tim, 1946- (New York : Broadway Books, 1998)
Related stories, linked by recurring characters and an interwoven plot, recreate an American foot soldier's experience in the Vietnam War.
School Library Journal.
Wilson's Fiction.
Wilson's Senior High School.
Booklist, June 2009.
Books for the Teen Age (NYPL), April 1998.
Library Journal, June 2009.
Keywords: Vietnam War, 1961-1975 -- Fiction; Vietnam War, 1961-1975 -- Veterans -- United States -- Fiction; Psychological fiction; Short stories; Vietnam War, 1961-1975 -- Fiction; War stories; Psychological fiction